2022
DOI: 10.61310/mndjstecbe.1043.22
|View full text |Cite
|
Sign up to set email alerts
|

Microhabitat Preference of Strombidae in Selected Intertidal Areas of Zamboanga del Norte and Misamis Occidental, Philippines

Justice Norhailyn P. Pangarungan,
Eloise Ann Kristine Makasiar,
Jessah P. Trillo
et al.

Abstract: This study aimed to identify the microhabitat preference of Strombidae species present in selected intertidal zones of Zamboanga del Norte and Misamis Occidental. A total of 406 individuals of Strombidae were collected and identified into 15 species. Most species of Strombidae were recorded to be abundant in seagrasses (Cymodocea rotundata and Thalassia hemprichii) and in algae (Gracilaria salicornia, Ulva lactuca and Ulva intestinalis). Strombidae were also observed along rocks, muddy sand, black sand, sedime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…However, Strombidae is affected by overexploitation caused by both natural and anthropogenic stressors, which leads to a large Natsir and Dillenia 2023). On the other hand, the other study in Zamboanga del Norte and Misamis Occidental, Philippines, showed that the most abundant species found in the selected area is the Canarium esculentum with 33.25% species, followed by the Canarium urceus with 17.49%, and the majority of the Strombidae species are found in the sandy-muddy substrate (Pangarungan et al 2022).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, Strombidae is affected by overexploitation caused by both natural and anthropogenic stressors, which leads to a large Natsir and Dillenia 2023). On the other hand, the other study in Zamboanga del Norte and Misamis Occidental, Philippines, showed that the most abundant species found in the selected area is the Canarium esculentum with 33.25% species, followed by the Canarium urceus with 17.49%, and the majority of the Strombidae species are found in the sandy-muddy substrate (Pangarungan et al 2022).…”
Section: Discussionmentioning
confidence: 93%
“…However, the T. sulcata and I. obsolete were commonly harvested in the H' = -∑ P i (ln P i ) decrease in the population of marine species (Stoner et al 2018;Ardila et al 2020). There are about 13 genera of Strombidae, with more than 50 different species reported that are found in the Philippines (Poppe 2008a(Poppe , 2008b, and these include the C. urceus (Pangarungan et al 2022) mangrove area of Guang-guang. These gastropods were collected by handpicking or using a small knife.…”
Section: Abundance Of Gastropodsmentioning
confidence: 99%